Peran Orang Tua dalam Mendorong Kreativitas Anak Usia Dini melalui Aktivitas Bermain di Rumah - Nurhasanah R (Sipakatau: Jurnal Pendidikan dan Kebudayaan, 2025)
This study aims to examine the role of parents in encouraging creativity in early childhood through play activities at home. Creativity is a crucial aspect of child development, influencing critical thinking, problem-solving, and self-expression. Parents, as the first educators in the family environment, play a central role in providing spaces and activities that support the development of children's creativity. Using a qualitative approach, this study employed in-depth interviews with parents of early childhood children and observations of parent-child interactions during play activities at home. The results indicate that parents who actively engage in children's play can create a stimulating environment for the development of creativity. Types of play that involve imagination, exploration, and creativity, such as role-playing and art, have been shown to be effective in enhancing children's creative abilities. Furthermore, sufficient time and the quality of parental interaction during play also positively influence the development of children's creativity. This study provides recommendations for parents to better understand the importance of play activities in supporting children's creative development and offers concrete strategies for creating more creative play activities at home. The results also provide insights for early childhood educators in designing programs that involve families to support children's creativity more holistically.